The structural overview of root and branch concept in transportation management planning - Ndikom, Obed (International Journal of Engineering and Technology, 2014)
This paper looks at the nature, structure, characteristics, scope and dimensional trends and operational functioning of root and branch concept of transportation management planning in any organization. The root and branch concept of transportation management planning is a process that connotes a managerial initiative of adopting a holistic bottom-up and top-down approach in managerial planning process. This concept is one that decides a systematic adoption of either bottom-up strategy or top-down approach in the management planning of a transport organization. This concept has a global view and honestly sees it as one that can’t be possible without the management of the internal operational mechanisms and dynamics at the end. Therefore, effort should be made to have a holistic structural overview of this emerging concept in dealing and managing internal issues in the organization.